2014
DOI: 10.1096/fj.13-244368
|View full text |Cite
|
Sign up to set email alerts
|

Prohibitin 2 represents a novel nuclear AKT substrate during all‐ trans retinoic acid–induced differentiation of acute promyelocytic leukemia cells

Abstract: The AKT/PKB kinase is essential for cell survival, proliferation, and differentiation; however, aberrant AKT activation leads to the aggressiveness and drug resistance of many human neoplasias. In the human acute promyelocytic leukemia cell line NB4, nuclear AKT activity increases during all-trans retinoic acid (ATRA)-mediated differentiation. As nuclear AKT activity is associated with differentiation, we sought to identify the nuclear substrates of AKT that were phosphorylated after ATRA treatment. A proteomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
42
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 61 publications
3
42
0
Order By: Relevance
“…On the other hand, the data presented by Bavelloni et al indicate that AKT1/2 also phosphorylates S91 during differentiation, and more importantly phosphorylation of S91 is required for survival in this cell model. The cellular death reported by Bavelloni et al following overexpression of a PHB2 (S91A) mutant was highly indicative of mitochondrial dysfunction and very similar to findings reported following the expression of PHB mutants lacking or containing alterations in the mitochondrial transmembrane domain (MTS), critical for mitochondrial localization (Fig. C).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…On the other hand, the data presented by Bavelloni et al indicate that AKT1/2 also phosphorylates S91 during differentiation, and more importantly phosphorylation of S91 is required for survival in this cell model. The cellular death reported by Bavelloni et al following overexpression of a PHB2 (S91A) mutant was highly indicative of mitochondrial dysfunction and very similar to findings reported following the expression of PHB mutants lacking or containing alterations in the mitochondrial transmembrane domain (MTS), critical for mitochondrial localization (Fig. C).…”
Section: Discussionsupporting
confidence: 80%
“…In addition to S91, S176 was also phosphorylated by AKT in this model system, although S176 phosphorylation was secondary to S91, suggesting a hierarchical phosphorylation. Interestingly, in this study, while exogenous expression of a S176A mutant had little effect on cell viability, exogenous expression of a S91A phospho‐mutant resulted in a rapid and complete apoptosis of NB4 cells within 24 h after transfection . Such apoptosis is a hallmark of mitochondria catastrophe and this phenotype matched those observed in embryonic stem cells in which the PHBs were knocked‐out and cell lines where PHBs were knocked‐down using siRNA (Fig.…”
Section: Introductionsupporting
confidence: 72%
“…Here, we show that primary blasts from APL patients express very low levels of AKT protein. It is known that PML deactivates and promotes degradation of nuclear AKT within nuclear bodies (PML‐NBs) (Salomoni & Pandolfi, ; Bavelloni et al , ). Thus, one could expect that in PML/RARA‐positive cells, where the function of PML‐NBs is impaired, nuclear AKT would promote survival over apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study using the human acute promyelocytic leukemia cell line, NB4, identified two substrates, the Serine/arginine-rich splicing factor 3 (SRSF3) and the prohibitin 2 (PHB2), which are associated with AKT/PBK pathway and their phosphorylation increased during in vitro activation with ATRA [28]. This, in turn, led to activation of AKT/PBK resulting in promotion of cell survival and differentiation vs. apoptosis [28]. …”
Section: 2 Induction Of Intra-cellular Signal Transduction Pathwaysmentioning
confidence: 99%